2008
DOI: 10.1124/jpet.108.145425
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Agonists Stimulate [3H]GABA Release in the Globus Pallidus of the Rat When GiProtein-Receptor Coupling Is Restricted: Role of Dopamine D2 Receptors

Abstract: The motor effects of cannabinoids in the globus pallidus appear to be caused by increases in interstitial GABA. To elucidate the mechanism of this response, we investigated the effect of the selective cannabinoid type 1 receptor (CB1) cannabinoid agonist arachidonyl-2-chloroethylamide (ACEA) on [ 3 H]GABA release in slices of the rat globus pallidus. ACEA had two effects: concentrations between 10 Ϫ8 and 10 Ϫ6 M stimulated release, whereas higher concentrations (IC 50 Ϸ 10 Ϫ6 M) inhibited it. Another cannabino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…Localization of D2R and CB1R in the same presynaptic terminal of striatum and globus pallidus has been demonstrated by autoradiographic techniques in the rat (Herkenham et al, ; Martín et el., 2008), suggesting an interaction in the modulation of GABAergic neurotransmission. Functional evidence for the effect of the CB1R/D2R relationship on GABAergic transmission in the pallidum has been reported by Gonzalez et al (). They found that the coactivation of these receptors produces an increase in GABA release by normal rats, possibly by a similar increase in cAMP formation (Glass and Felder, ; Jarrahian et al, ; Khan and Lee, ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Localization of D2R and CB1R in the same presynaptic terminal of striatum and globus pallidus has been demonstrated by autoradiographic techniques in the rat (Herkenham et al, ; Martín et el., 2008), suggesting an interaction in the modulation of GABAergic neurotransmission. Functional evidence for the effect of the CB1R/D2R relationship on GABAergic transmission in the pallidum has been reported by Gonzalez et al (). They found that the coactivation of these receptors produces an increase in GABA release by normal rats, possibly by a similar increase in cAMP formation (Glass and Felder, ; Jarrahian et al, ; Khan and Lee, ).…”
Section: Introductionmentioning
confidence: 75%
“…However, other receptors, such as CB1R, are also present in these striatopallidal neurons (Chaves‐Kirsten et al, ; Herkenham et al, ; Julian et al, ). CB1R are also coupled G i/o proteins that inhibit GABA release (Gonzalez et al, ; Köfalvi et al, ) and they also contribute to the control of motor behavior, as was shown in the striatum and the globus pallidus (González et al, ; Kelsey et al, ; Souilhac et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are based on the role of endocannabinoids as key modulators of DAergic neurotransmission in the basal ganglia [253][254][255]. Notably, CB 1 receptors are abundantly expressed in striatal neurons [256][257][258][259] and interact with both D 1 and D 2 receptors [260,261]. Preliminary evidence suggests that the combined activity of ATSs and cannabinoids may have differential effects on these two receptors.…”
Section: Mechanisms Of Interactions Of Cannabinoids and Atssmentioning
confidence: 96%
“…On the other side, D 2 receptors controlled anandamide production in the striatum. This may serve as an inhibitory feedback mechanism counteracting dopamine‐induced facilitation of psychomotor activity (Giuffrida et al ., ), as well as controlling G i/o protein availability for CB 1 receptors (González et al ., ) and facilitating endocannabinoid‐mediated long‐term synaptic depression of GABAergic neurons (Kreitzer and Malenka, ), an effect also seen in the ventral tegmental area (Pan et al ., ). A similar interaction of endocannabinoids with D 1 receptors has been recently proposed (Martín et al ., ) and this proposal has been extended to glutamatergic synapses in which dopamine and its receptors also promote endocannabinoid‐mediated synaptic depression (see Lovinger and Mathur, ).…”
Section: Cannabinoid–dopamine Interactions At the Basal Gangliamentioning
confidence: 99%